Campo multiplicativo: estratégias de resolução de problemas de divisão de alunos do 4º ano do Ensino Fundamental em escolas públicas de Maceió - Lima, Rosemeire Roberta de (2012)
In this research of qualitative approach, in the format of case study, different problem-solving strategies for division were investigated - ideas of partition and quoticao used by students of the 4th year of elementary school. A hundred and five students, aged between eight and 14 years old, from three public schools in Maceio, have taken part of the research. These students have solved four problem-situations, being three problems of division by quota and one problem of partition. We have based our analyses in the studies of Vergnaud (2009), Pozo (1998), Starepravo (1997), Itacarambi (1997), Carvalho (2007, 2010), Walle (2009), Dixon (1997), Nunes et al (2002), Smole and Diniz (2001), Caraca (1984), among others. The results have indicated that students in their early years of Elementary School do not experience the work with problem solving and their strategies reveal that they have based their answers on the table of multiplication and/or on the continuity of the reasoning of the additive field the use of adding repeated plots- and that the ideas of partition, action of distributing equally, was more present in the proposed problems solutions, not showing differentiation between the ideas of partition and quoticao. Besides that, the students ' answers demonstrate that during their schooling they had no contact with proposals for math activities that demand moments of justifications for their answers. This fact shows the absence of the specificity of mathematical language. Such an absence indicates that in Mathematics what does matter is the use of calculations and that the natural language is a specific study of the Portuguese Language subject. Such a vision just contributes to the importance of working problemsolving, so that enunciations can be understood and that the students, in their turn, explicite various strategies of resolution, choosing the most economic ones, and that their decisionmaking can be coherent to their mathematical thinking.